Pengaruh Jus Apel Terhadap Penurunan Tekanan Darah pada Lansia Hipertensi di Puskesmas Muara Kaman - Siti Khoiroh (Universitas Muhammadiyah Kalimantan Timur, 2017)
Background : Hypertension is a condition of high blood pressure in the arteries that lasted continuously for the long term. Hypertension can be overcome in two ways: pharmacology and non-pharmacology. Pharmacology treatment usually use medicine while one of the ways for non-pharmacology treatment is to consumes apple juice.Research Objective : The aim of this research is to know the effect of apple juice on blood pressure decrease in elderly people with hypertension at Muara Kaman Community Health Center.Methods : The design of this research used quasi experimental design (quasi experiment) with pretest posttest control group design. The sample of the research was hypertensive respondents at Muara Kaman Community Health Center as many as 30 respondents were divided into 2 groups, 15 intervention groups and 15 control groups. The sampling technique used purposive sampling. The research instruments were stethoscope and sphygmomanometer, data analysis using t test dependent and t test independent.Results : There were a significant influence between pretest and posttest of apple juice in the intervention group (P value = 0,000; P <0.005). The mean difference in systolic blood pressure in the intervention group and the control group also had significant differences (P value = 0.002; P <0.05), where as the mean difference in diastolic blood pressure in the intervention group and the control group also had significant differences (P value = 0,039; P <0,05).The Conclusions : The results of this research showed that consumes apple juice gives an effect on the blood pressure of hypertensive patients by consumes regularly.The Suggestions : Nurses and the public can use apple juice as one of the ways to handling to hypertension sufferers besides antihypertensive drugs.